B-Spline Collocation Solution of One Dimensional Nonlinear Differential Equation Arising in Homogeneous Porous Media - et al., Nilesh Sonara (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper investigates the Numerical solution nonlinear partial differential equation for one dimensional instability phenomenon known as Boussinesq's equation arising in a porous media in oil-water displacement treatment (instability). Its Numerical Solution has been acquired by utilizing B-Spline method with proper boundary and initial conditions. The Numerical solution of Boussinesq's equation using Spline method is very nearer to Exact Solution obtained by analytical method .It is surmise that when distance and time increases, its saturation of injected water is increases . Numerical solution and graphical illustration has been obtained by Matlab.